2006
DOI: 10.1111/j.1469-8137.2006.01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Large variation in whole‐plant water‐use efficiency among tropical tree species

Abstract: Summary• It is well known that whole-plant water-use efficiency (transpiration efficiency of carbon gain, TE C ) varies among plant species with different photosynthetic pathways. However, less is known of such variation among tree species within the C 3 group. Here we measured the TE C of seven C 3 tropical tree species. Isotopic analyses ( δ 13 C, δ 18O, and δ 15 N) and elemental analyses (carbon and nitrogen) were undertaken to provide insight into sources of variation in TE C .• Plants were grown over seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
85
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 58 publications
(79 reference statements)
13
85
2
3
Order By: Relevance
“…This is consistent with previous results showing large variation in TE c among seven tropical tree species (Cernusak et al, 2007a). When the TE c for each individual plant was normalized according to its growth-weighted mean daytime vapor pressure deficit, D g , the variation among species was still apparent, suggesting that D g was not a primary control over TE c .…”
Section: Transpiration Efficiencysupporting
confidence: 80%
“…This is consistent with previous results showing large variation in TE c among seven tropical tree species (Cernusak et al, 2007a). When the TE c for each individual plant was normalized according to its growth-weighted mean daytime vapor pressure deficit, D g , the variation among species was still apparent, suggesting that D g was not a primary control over TE c .…”
Section: Transpiration Efficiencysupporting
confidence: 80%
“…7, C and D; Table I). This agrees with previous observations for a smaller number of species (Cernusak et al, 2007a(Cernusak et al, , 2008(Cernusak et al, , 2009b. When plants were grown in fertilized soil, the legume species appeared to lose their advantage in W P , as shown for the comparison between O. macrocalyx and S. macrophylla in this study (Fig.…”
supporting
confidence: 82%
“…Taking the nonnodulating legume S. parahyba as a reference plant (Pons et al, 2007) and assuming a discrimination of 1‰ during N 2 fixation (Yoneyama et al, 1986), we estimated the proportion of plant N acquired by N 2 fixation to be 84% for O. macrocalyx, 73% for A. adinocephala, 52% for D. retusa, 46% for I. punctata, and 0% for S. parahyba. However, these values should be considered as indicative only, because the non-N 2 -fixing species included in the study showed a relatively large range of plant d 15 N, similar to previous observations for non-N 2 -fixing tropical tree species (Guehl et al, 1998;Cernusak et al, 2007aCernusak et al, , 2009cPons et al, 2007). This introduces uncertainty into the estimate of d 15 N for soil-derived plant N (Shearer and Kohl, 1986).…”
mentioning
confidence: 71%
“…High variation in CID has been found across species (for example, Oliveras et al, 2003 for conifers;Cernusak et al, 2007 for tropical trees), as well as moderate narrowsense (h 2 ) heritability within-species (0.17 in maritime pine, Brendel et al, 2002; 0.09 across-sites in loblolly pine, Baltunis et al, 2008). As trees with higher WUE may sustain growth under water-limitation conditions and differences in WUE represent also different growing strategies, CID is an attractive trait for breeding, in particular in dry areas or in those regions in which the higher impact of the current process of global climate change will be felt.…”
Section: Discussionmentioning
confidence: 99%